SCANNING LINGKUNGAN EKSTERNAL DAN INTERNAL LEMBAGA PENDIDIKAN ISLAM - Anisa Febriyanti (Institut Agama Islam Negeri Purwokerto, 2017)
Education was always faced with the problem of the complex, start from the competition in the management of education institutions, leadership, finance staffing, curriculum community support and the level of trust. Adult private schools is growing rapidly along with the needs of the community will be better quality education. Private schools based on Islam is currently has become a trend by the users of education along with the demands and changes of the age.The changes occur in the environment education institutions requires a paradigm shift in respect of the environment around. In order to achieve their aims and various mission of an educational institution, then the interaction between stakeholders that there must be intertwined with one another. External and internal environment in the educational institution must be understood by all the stakeholders. The introduction of the internal and external environment in the right educational institutions, then will affect the strategic decision makers about the direction that will be taken and the action to be taken in order to make the innovation of education institutions which they manage.